Ways of knowledge in Plotinus - Santa Cruz, María Isabel (Estudios de Filosofía, 2006)
After a brief introduction destined to bring mind the great lineaments of the Plotinian System, this paper analices three ways of knowledge or of apprehension that characterize the three levels of reality or hipostasis. On the level of intelligence, nous, which is determined as nouetical level, is verified a type of genuine knowledge, which is auto-knowledge. At the level of the soul, psyché, the dianoetical level, there is a type of knowledge of a discursive type that only in a secondary sense and in a denvated one is knowledge of itself. Lastly, on the level of the One, tó hèn, the supranoeticol level, can we speak of a knowledge of the self only in the traslaticious sense and "eminential”, since the first principle of reality, which is absolute unity, having no duplicity whatsoever, in a strict sense cannot have thought, not even of the self but, at the same time, is not inherent, but is absolute fullness. This paper tries to show how Plolinus finds support in the type ofknowledge of the intelligence, which serves him as a central point, to articulate the three types of knowledge and to characterize an "infra-self-knowledge ", that of the soul, and a “supra- setf-knowledge”, that of the One.